Characterization Of Superparamagnetic Iron Oxide Nanoparticles With Different Surfactants - In Search Of Optimum Synthesis Parameters For Mri Application - Noqta, Osama Ahmad Salameh Abu (2018)
Superparamagnetic iron oxide nanoparticles (SPIONs) have been extensively studied for various biomedical applications, such as magnetic resonance imaging (MRI) contrast agents, and hyperthermia. The most common approach used to produce SPIONs is co-precipitation method. However, problem due to agglomeration and the broad size distribution of nanoparticles prepared by co-precipitation method hinder their application progress in MRI. Therefore, this study aims to produce a highly stabilized and monodispersed SPIONs for MRI contrast agents. In this thesis, SPIONs were synthesized with different surfactants (tri-sodium citrate, polyvinylpyrrolidone (PVP), chitosan, cetyl trimethylammonium bromide (CTAB) and citric acid) using the one pot co-precipitation method for surface modification and to ensure excellent colloidal stability in water. In addition, the synthesis parameters such as surfactant concentration, pH, and temperature of reaction were optimized to obtain stabilized SPIONs. The SPIONs prepared in the presence of tri-sodium citrate formed the most stable SPIONs due to improved physiological condition, dispersion and stabilization in aqueous solution. In addition, citrate-SPIONs displayed the highest zeta potential (ζ= -44.0 mV) and saturation magnetization (Ms=53.9 emu g-1) compared with other samples, due to the ability of three carboxylate groups dissociated from the citrate to strongly bind to the surface of SPIONs. The TEM measurements of the different SPIONs indicated that the type of surfactant affects their average particle sizes and size distribution. In addition, the presence of defects within the spinel structure, i.e., oxidation of the SPIONs, seems to be also influenced by the choice of surfactant.